Understanding Employee Performance Through Job Training, Career Development, and Organizational Culture: A Structural Model Approach - Niken Wulan Rahayu; Subiyanto , Didik; Kusuma, Nala Tri (Universitas Muhammadiyah Pontianak, 2026)
This study investigates the influence of job training, career development, and organizational culture on employee performance at PT. Dekor Asia Jayakarya, a bamboo and wood decoration manufacturer with 99% export orientation. Using a quantitative descriptive approach and saturated sampling of 50 employees, data were collected via questionnaires. The results show that job training and career development do not significantly affect performance. However, organizational culture has a positive and significant impact, highlighting the role of shared values and norms in enhancing employee effectiveness.